Occupant-centric building design: Human factors and energy consumption in sustainable offices - Bodin, Emil; Karlsson, David (My University, 2026)
Buildings consistently consume more energy in operation than predicted during de sign, a discrepancy known as the energy performance gap. A key contributor is the reliance on standardised occupancy assumptions that fail to capture actual occu pant behaviour. This study investigates the influence of three human factors on the energy performance of a modern, WELL and BREEAM Excellent certified office building in Gothenburg, Sweden: occupancy patterns, internal electrical loads, and solar shading behaviour. The Energy-Data-Driven Occupancy Schedule (EDDOS) methodology was applied to derive data-driven occupancy and equipment schedules from one full year of mea sured tenant electricity data. A sensitivity analysis was conducted on occupancy density, testing scenarios from the SVEBY standard assumption of 20 m2 per per son to 1000 m2 per person, representing post-pandemic hybrid working conditions. Solar shading behaviour was evaluated using two behavioural archetypes based on the Lightswitch-2002 model, and a glazing sensitivity analysis was performed across three solar heat gain coefficients (g = 0.26, 0.40, 0.60). The results demonstrate that occupancy density is the primary driver of the per formance gap, while the temporal variation captured by the EDDOS schedule and solar shading behaviour both have marginal influence on district heating demand. Reducing occupancy density to reflect post-pandemic hybrid working patterns sub stantially closes the gap between simulated and measured district heating consump tion. Solar shading behaviour is found to have negligible energy impact across all glazing specifications tested, consistent with the building’s fully automated shading system. These findings suggest that in modern, highly automated office buildings, occu pancy density uncertainty associated with hybrid working represents a more signif icant source of simulation error than occupant behavioural patterns. Standardised assumptions such as those prescribed by SVEBY may systematically underestimate the performance gap in contemporary hybrid offices.
Keywords: energy performance gap; occupant behaviour; occupant-centric design; building energy simulation; EDDOS; occupancy density; hybrid working; IDA ICE; SVEBY; solar shading